PENGALAMAN KOMUNIKASI INTERPERSONAL MAHASISWI DAN PERSEPSINYA TERHADAP KREDIBILITAS DOSEN DI KAMPUS BERBASIS ISLAM: STUDI PADA PROGRAM KOMUNIKASI UNIVERSITAS HALIM SANUSI - Robby Rachman Nurdiantara; Sitti Maesurah (AN-NISA, 2025)
This study explores female students’ interpersonal communication experiences and their perceptions of lecturer credibility at an Islamic-based campus, Universitas Halim Sanusi, focusing on the communication studies program. The study aims to identify patterns of interpersonal communication between female students and lecturers at an Islamic-based campus, analyze students’ perceptions of lecturer credibility, explain the impact of lecturer credibility on students’ learning experiences and engagement, and examine the role of Islamic values in shaping academic interpersonal communication. A descriptive qualitative approach was used to investigate female students’ communication experiences and how they interpret lecturer credibility in academic interactions. The findings indicate that communication patterns between female students and lecturers at an Islamic-based campus balance interpersonal closeness and professional boundaries, with lecturer credibility encompassing competence, integrity, and care. Supportive and consistent interactions enhance students’ psychological safety, motivation, and active participation. Islamic norms and values frame communication behavior, reinforcing an ethical and conducive learning experience. Female students perceive lecturer credibility as an integrated experience formed by academic competence, integrity, consistency, interpersonal care, material relevance, contextual communication skills, and Islamic values. Lecturer credibility influences learning motivation, active participation, psychological security, academic aspirations, and the quality of classroom and mentoring interactions. Lecturer credibility plays a key role in shaping positive academic experiences for female students through several dimensions, including material consistency, communication openness, attention and care, and the ability to adjust interactions according to students’ characteristics. Islamic-based campus values and norms shape female students’ communication with lecturers to be polite, professional, and productive. Islamic principles, including adab (etiquette), amanah (trustworthiness), honesty, and patience, provide an ethical framework that governs language, interaction boundaries, and communication adjustments based on gender context.